2021
DOI: 10.22454/primer.2021.619838
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Confidence With Electronic Health Record Order Entry

Abstract: Introduction: Despite near-universal utilization of electronic health records (EHRs) by physicians in practice, medical students in most ambulatory settings gain limited experience with placing EHR orders. In this study, an individual preceptor site investigated the usefulness of a targeted curriculum in improving students’ EHR confidence and clinical reasoning skills. Methods: Family medicine clerkship students assigned to one community health center were invited to participate in this prospective, survey-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Sarkar and colleagues found that deliberate practice with feedback in performing EHR skills resulted in improved accuracy of single orders placed by students. 24 Additionally, 87% of graduates from two of the participating Core EPA Pilot Project institutions were deemed to be prepared to perform EPA 4 skills by their residency program directors. 4 These studies suggest that intentional instruction and feedback can result in entrustment.…”
Section: Discussionmentioning
confidence: 99%
“…Sarkar and colleagues found that deliberate practice with feedback in performing EHR skills resulted in improved accuracy of single orders placed by students. 24 Additionally, 87% of graduates from two of the participating Core EPA Pilot Project institutions were deemed to be prepared to perform EPA 4 skills by their residency program directors. 4 These studies suggest that intentional instruction and feedback can result in entrustment.…”
Section: Discussionmentioning
confidence: 99%
“…21 On the other hand, if multiple clinical sites do not offer one EHR system, individually targeted instruction by faculty and preceptors is needed to facilitate student competency. 22,23 Some of the barriers preventing students from full access to EHRs during clinical training include concerns over the privacy of patient information due to the Health Insurance Portability and Accountability Act, potential legal liability due to billing errors, institutional costs, and lack of resources and time to provide institution specific EHR training. 18,24 Contributing to these barriers, Medicare has restrictive guidelines regarding electronic charting, which pose a substantial challenge for students.…”
mentioning
confidence: 99%
“…Academic programs with the advantage of using one EHR system offered in various clinical settings can provide graduates the opportunity to be competent in EHR documentation 21 . On the other hand, if multiple clinical sites do not offer one EHR system, individually targeted instruction by faculty and preceptors is needed to facilitate student competency 22,23 …”
mentioning
confidence: 99%